HDLBP-stabilized lncFAL inhibits ferroptosis vulnerability by diminishing Trim69-dependent FSP1 degradation in hepatocellular carcinoma - Yuan, Jingsheng; Lv, Tao; Yang, Jian; Wu, Zhenru; Yan, Lvnan; Yang, Jiayin; Shi, Yujun (Redox biology, 2022)
Recent studies have suggested that exploring the potential mechanisms regulating ferroptosis vulnerability may contribute to improving the systemic therapeutic efficacy in HCC. High-density lipoprotein-binding protein (HDLBP), the largest RNA-binding protein, is an important transporter that protects cells from overaccumulation of cholesterol, but few studies have elucidated the role of HDLBP in the regulation of ferroptosis vulnerability in HCC. Our study suggests that HDLBP was markedly elevated in HCC compared with noncancerous liver tissues and that this elevation inhibited the ferroptosis vulnerability of HCC. Further experiments revealed that HDLBP bound to and stabilized the long noncoding RNA lncFAL (ferroptosis-associated lncRNA), which is derived from the plexin B2 gene. Moreover, our study suggests that the splicing of lncFAL was increased by YTH N6-methyladenosine (m6A) RNA-binding protein 2 (YTHDF2) in a m6A-dependent manner. Although HDLBP or lncFAL could not regulate the GPX4 antioxidant signalling pathway, lncFAL reduced ferroptosis vulnerability by directly binding to ferroptosis suppressor protein 1 (FSP1) and competitively abolishing Trim69-dependent FSP1 polyubiquitination degradation. More importantly, FSP1 inhibition promoted the antitumour activity of ferroptosis inducers both in vitro and in vivo. Collectively, our results provide a clinically promising demonstration that HDLBP stabilizes lncFAL, which mediates a FSP1-dependent anti-ferroptosis mechanism in HCC. These results support the enormous potential of disrupting FSP1 as a promising therapeutic approach for HCC patients with high HDLBP or lncFAL expression. [Display omitted] •HDLBP inhibits the ferroptosis vulnerability of HCC by stabilizing LncFAL.•Splicing of LncFAL is increased by YTHDF2 in a m6A-dependent manner in HCC.•LncFAL inhibits FSP1 polyubiquitination by disrupting the FSP1-TRIM69 interaction.•FSP1 blockade is essential for the induction of ferroptosis in HCC.•LncFAL is positively related to FSP1 and as an independent prognostic biomarker.